Towards sustainable tourism : analysis of stakeholder perspectives in Baltistan, Pakistan - Hassan, Muhammad Wajahat (2021)
The importance of the tourism industry is explicitly highlighted in United Nation’s SDGs. Sustainable tourism development is recognized as a useful tool for poverty reduction, social justice, environmental protection, and gender equality. Tourism is also one of the fastest-growing industries, providing employment opportunities to a large number of the world population, especially to the local people; women; and youth. The tourism industry has shown tremendous growth during the last six years in Baltistan. Therefore, to receive long-term benefits, detailed research was needed to study the impacts of tourism growth on the sustainability of the industry. Despite the immense tourism potential, the tourism industry of Baltistan has remained neglected by the Government of Pakistan, due to the disputed status it has. The tourism sector can bring revolutionary changes to the life of local inhabitants by formulating effective tourism policies. The scientific analysis based on actual market knowledge is essential to take right decisions. For this purpose, to generate local tourism knowledge, this study identifies the key stakeholders of the Baltistan tourism industry, the importance of tourism for the local population, the nature of current practices, and the problems preventing sustainable tourism growth from the perspectives of important stakeholders. Furthermore, this paper also provides detailed and relevant tourism knowledge from the literature, which include the evolutionary stages of tourism; the concept of sustainable tourism; and how tourism contributes to sustainable development. Qualitative methods were employed to conduct this research. For data collection, structured and unstructured interviews; and fieldwork methods were used. This paper concluded that increased tourism activities are generating several problems posing threat to the sustainability of the industry. Lack of research in this field was found the biggest hurdle in the formulation of effective policies. Lastly, this study recommends that constant monitoring of impacts is needed, and necessary remedial interventions are essential to reap the full benefits of tourism for a maximum period.